Laparoscopic surgical treatment of ovarian cancer: Stage IA. Communication of the first intervention in Latin America - Molina, Ernesto (2015)
One of the future goals of laparoscopic surgery is the field of gynecologic oncology. This field does not escape ovarian cancer whose curative surgical treatment in early stages can be approached with laparoscopic surgery. Since Reich et al. They reported the first case of laparoscopic removal of an ovarian carcinoma, demonstrating that can be accomplished laparoscopically, various objectives of ovarian cancer surgery, including appendectomy, omentectomy, cytologic sampling and peritoneales1 is printed laparoscopic surgical treatments in stadiums more They advanced, including exploration and excision of para-aortic lymph nodes.